STUDI VARIASI BERAT KATALIS WO3-SBE DALAM PROSES SONOKATALITIK METHYLENE BLUE - Wilsoma, Wilsoma; Hindryawati, Noor; Subagyono, R.R. Dirgarini Julia Nurlianti (Jurusan Kimia FMIPA UNMUL, 2019)
Degradations of methylene blue by sonocatalytic method using Spent Bleaching Earth (SBE) impregnatedwith WO3 have carried out. The stages of this study included SBE preparation, activation with H2SO4, modificationof WO3 with SBE through wet impregnation processes and sonocatalytic testing. WO3-SBE was characterizedusing XRD. XRD diffraction patterns of WO3-SBE showed the appeareance of WO3 peak at 28.855Â°; 34.813Â° 2Î¸.The degradation percentage of methylene blue (catalyst weight of 0.15 gram, methylene blue concentration 100ppm and contact time 15 minutes) was 99.12%.